Intestinal fungi and antifungal secretory immunoglobulin A in Crohn’s disease - Sun, Meng; Ju, Jingyi; Xu, Hongzhen; Wang, Yufang (Frontiers in Immunology, 2023)
Human gastrointestinal tracts harbor approximately trillions of commensal microorganisms. Emerging evidence points to a possible link between intestinal fungal dysbiosis and antifungal mucosal immunity in inflammatory bowel disease, especially in Crohn’s disease (CD). As a protective factor for the gut mucosa, secretory immunoglobulin A (SIgA) prevents bacteria from invading the intestinal epithelium and maintains a healthy microbiota community. In addition, in recent years, the roles of antifungal SIgA antibodies in mucosal immunity is becoming increasingly recognized, including regulating intestinal immunity by linking to hyphae-associated virulence factors. Here we review current knowledge on intestinal fungal dysbiosis and antifungal mucosal immunity in healthy individuals and in patients with CD, discuss the factors governing antifungal SIgA responses to intestinal mucosa in the latter group, and highlight potential antifungal vaccines targeting SIgA to prevent CD.